Silage Quality of King Grass (Pennisetum purpureophoides) Treated with Epiphytic Lactic Acid Bacteria and Tannin of Acacia - B Santoso; B Tj Hariadi; H Manik; H Abubakar (Media Peternakan, 2011)
The aim of this study was to evaluate the silage quality of king grass (Pennisetum purpureophoides) treated with addition of epiphytic lactic acid bacteria (LAB) prepared from fermented grass extract (FGE) or combined with tannin of acacia. Experiment was arranged to a completely randomized design with six treatments and three replications. Treatments were (A) king grass without additive as a control; (B) king grass + 3% (v/w) of FGE; (C) king grass + 3% (v/w) of FGE + 10 ml of acacia extract (50 g/100 ml); (D) king grass + 3% of FGE (v/w) + 10 ml of acacia extract (50 g/75 ml); (E) king grass + 3% of FGE (v/w) + 10 ml of acacia extract (50 g/50 ml), and (F) king grass + 3% of FGE (v/w) + 10 ml of acacia extract (50 g/25 ml). About 250 g of silage materials were ensiled in 400 ml bottle silos at room temperatures (approximately 28 °C) for 30 days. Variables measured were characteristics of FGE, fermentation characteristics and chemical composition of silage. Data were analyzed by analysis of variance and the significance differences among means were tested by the Duncan's multiple range test. Results showed that the number of lactic acid bacteria in FGE increased from 0.8 × 107 cfu/ml to 2.9 × 107 cfu/ml after 2 days anaerobic incubation. Concentration of lactic acid in silages with addition of FGE or combined with tannin of acacia (B, C, D, E, and F) were higher (P3-N decreased with increasing concentration of tannin. Butyric acid concentration decreased in silages B, C, D, E, and F as compared to that in silage A. Addition of FGE combined with tannin prepared from acacia leaf improved fermentation quality of king grass silage.